PRINCIPLES OF INTERCULTURAL COMMUNICATION IN TEACHING LITERARY TRANSLATION - Djumaniyazova Nargiza (Journals Park Publishing, 2023)
The article deals with the need to take into account the peculiarities of the process of intercultural communication while teaching literary translation as principles and develop the methodology of teaching literary translation, aimed at the cultural and linguistic identity.
Keywords: competence, psycholinguistic specificity, perception, inaccuracy, pedagogical influence, analyze shortcomings, students’attitude.